Uniform Convergence of Fourier Series on Compact Subsets - Kucukaslan, M.; Abdullayev, F. G. (Sarajevo Journal of Mathematics, 2024)
In this paper, the speed of approximation of $ω _{n}(B;f,z)$ to zero has been calculated by using analytic and geometric properties of the boundary of the given region, where $B$ is a subset of $G$ (a finite simpy connected domain bounded by a Jordan curve) and $ω _{n}=\left\vert f(z)-S_{n}(f,z)\right\vert ,~z\in B.$ 2000 Mathematics Subject Classification. 41A10, 30E10, 42A16